Concept paper on the awareness of 'fair dealing' among learners of Sunway College Johor Bahru. - Krishnaveni Sritharan, *; Mangair Karasi Manickam, * (2013)
The Copyright Law was enacted to encourage continuous creative work among academicians. In this age of technology, the knowledge and awareness of Copyright Law and its defence of fair dealing is becoming increasingly significant in protecting the academicians’ work. The aim of this concept paper is to understand the principle of Copyright Law and fair dealing in literary work. Furthermore, knowledge and awareness of Copyright Law and fair dealing among the learners will be studied. The study will be carried out with the learners of Sunway College Johor Bahru. The study will utilise a quantitative method to analyse the learners’ understanding of the knowledge and awareness of Copyright Law and fair dealing. The study is important to show the level of awareness portrayed among learners of Sunway College Johor Bahru.